Haiti : Interim Poverty Reduction Strategy Paper; Joint Staff Advisory Note. (IMF Staff Country Reports; Country Report ;, 2007)
This Joint Staff Advisory Note focuses on the Interim Poverty Reduction Strategy Paper (I-PRSP) for Haiti. The I-PRSP outlines the main areas of actions envisaged by the authorities to reduce poverty as well as the steps to be undertaken in the preparation of the full Poverty Reduction Strategy. The I-PRSP presents a good diagnostic of the current dimensions of poverty in Haiti. It also covers well the authorities' macroeconomic objectives and the broad measures necessary to reach these objectives.